The use of time to maximum enhancement to indicate areas of ablation following the treatment of liver tumours with high-intensity focused ultrasound. - Noterdaeme, O; Leslie, T; Kennedy, J; Phillips, R; Brady, M (2009)
The aim of this study was to investigate the use of time to maximum enhancement (t(max)) for each voxel in contrast-enhanced MRI (CE-MRI) as a non-invasive tool to determine areas of necrosis following treatment of liver tumours with high-intensity focused ultrasound (HIFU) and, having established the utility of t(max) maps, to develop a three-dimensional (3-D) representation to display this information concisely. 3-D T(1) weighted fast spoiled gradient echo images of the liver were acquired before and after administration of contrast agent. The CE-MR images were aligned to the pre-contrast volume and an estimate of t(max) was obtained for each voxel. Such pre- and post-contrast image sets were acquired before and after ablation. The t(max) maps before and after HIFU treatment were correlated with the procedure notes, radiological reports and gross histological specimen. Finally, 3-D t(max) maps of the whole liver were reconstructed to show all areas of abnormal tissue perfusion. Normal, healthy liver tissue uniformly enhances maximally after approximately 1 min. The computed t(max) maps accurately delineated areas of abnormal contrast agent uptake, corresponding to tumour deposits. Changes in t(max) and non-enhancing voxels after treatment correlate well with volumes targeted during ablation and the necrotic regions seen on gross histological specimens. Alignment of the contrast-enhanced images with the pre-contrast volume greatly improved the conspicuity of the t(max) maps. We conclude that t(max) maps and their 3-D views can be used as a non-invasive tool to assess and potentially to quantify the success of HIFU ablation, and concisely represent the large number of CE-MRI data.